The Effects of Supplementing Lysophosphatidylcholine in Diet on Production Performance, Egg Quality and Intestinal Morphology of Laying Hens - Juntanapum, Witchanun; Poeikhampha, Theerawit; Poungpong, Kanokporn; Rakangthong, Choawit; Kromkhun, Pudcharaporn; Bunchasak , Chaiyapoom (International Journal of Poultry Science, 2019)
Background and Objective: This study was conducted to evaluate the effects of supplementation of Lysophosphatidylcholine (LPC) in diets on production performance, egg quality and intestinal morphology of laying hens. Materials and Methods: A total of 288 commercial laying hens (Lohmann brown-classic) from 33-46 weeks of age were used in this study. The hens were divided into 3 groups of 8 replications with 12 hens each. According to the experimental groups, hens were fed as 1) control diet, 2) control diet with 0.05% LPC and 3) control diet with 0.10% LPC. Results: At the end of the trial, supplementations of LPC (0.05 and 0.10%) significantly improved feed conversion ratio (FCR), increased egg size, decreased feed intake and reduced feed cost per egg weight (FCE) (p<0.01), although significant effect on percentage of egg production, egg weigh and egg mass were not observed. Neither of internal and external egg qualities were influenced by LPC supplementation. In term of morphology, adding LPC significantly decreased villi height in the segment of duodenum and conversely increased in the jejunum (p<0.05). Conclusion: It is concluded that supplementation of LPC may improve nutrients utilization (digestion or/and absorption) via the modification of gut morphology.